Hydrocarbon-biodegradation potential of tropical fungi isolated from oil-contaminated sediments in Estancia and Batad, Iloilo - Niego, Allen Grace T. (University of the Philippines Visayas, 2015)
The study generally aimed to isolate indigenous fungal flora from oil contaminated beach and mangrove sols in Estancia and Batad, Iloilo affected by NPC 103 Oil spill in November 8, 2013 and evaluate their hydrocarbon degradation potentials singly or in consortia. Specifically, it aimed to (1) isolate and correspondingly describe the indigenous fungal flora from beach and mangrove areas of oil contaminated sites in conjunction with (a) species frequency of occurence per site, (c) Shannon index of diversity and evenness, and (d) Jaccard Similarity Indx ; (2) screen hydrocarbon (HC)-degrading fungi using Bushnell Haas medium supplemented with sterile crude oil as sole carbon source ; and (3) evaluate selected isolates (singly and in consortia) from the bh medium for degradation of (a) total petroleum hydrocarbon (TPH), (b) Polycyclic Aromatic hydrocarbon (PAHs), (c) alkane using Gas Chromatography-Mass Spectrometry. A total of 20 fungal species were identified in this study mostly dominated by mitosporic or anamorphic fungi belonging to the genera of Acremonium, Aspergillus, Cladosporium, Curvularia, Monilia, Paecilomyces, Penecillium, Trichoderma, Verticillium and Yeast. Aspergillus fumigatus got the highest frequency of occurence (43.0%) among all species. Penecillium sp 1 (EB331) got the highest value for individual category on TPH (64.7%) and PAH (43.4%)degradatin. The consrtium of Aspergillus fumigatus and paecilomyces sp1, a=D obtained the highest values of 69.4% and 66.6% on the degardation of TPH and PAH with the increased efficacy of 13.6% and 42.4% on two species consortia. The current data clearly demonstrated the hydrocarbon biodegradation potential of tropical fungi isolated from oil contaminated habitats useful for future bioremediation activities.